Lidocaine ameliorates chronic constriction injury-induced neuropathic pain through regulating M1/M2 microglia polarization - Yuan Jiaqi; Fei Yue (Open Medicine, 2022)
This study is intended to explore the mechanism that lidocaine ameliorates chronic constriction injury (CCI)-induced neuropathic pain (NP) related to the polarization of M1 and M2 microglia. CCI rats were established by surgery to induce NP. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) of rats were determined. Microglial line HAPI cells were polarized into M1 or M2 cells using lipopolysaccharide (LPS) or interleukin (IL)-4, respectively. Immunofluorescence staining was performed to determine the Iba1/CD86- and Iba1/CD206-positive cells. Markers of M1 and M2 microglia were assessed using flow cytometry. Real-time polymerase chain reaction and enzyme-linked immunosorbent assay were performed to detect the level of mRNA and inflammatory factors. Lidocaine ameliorates CCI-induced NP, evidenced by the markedly increased values of MWT and TWL in NP rats. Lidocaine inhibited M1 microglia polarization but promoted M2 microglia polarization in a rat model of CCI-induced NP. Besides, in the in vitro experiment, lidocaine regulated M1/M2 polarization in LPS- or IL-4-treated HAPI microglia. Lidocaine ameliorates CCI-induced NP by regulating M1/M2 microglia polarization. This study investigated the biological role of lidocaine in regulating NP in rats, which may be helpful for revealing the pathogenic mechanisms of NP and provide a potential therapeutic factor.